Tribological and cutting performance of TiAlCrN films with different Cr contents deposited with multilayered structure. (March 2018) - Fernandes, F.; Danek, M.; Polcar, T.; Cavaleiro, A.
Abstract: Increasing requirements on high speed and dry cutting applications open up new demands on the quality of cutting tool materials. In this study, we evaluated the effect of Cr additions on the properties of Ti(Al)N/Cr(Al)N multilayered films deposited by magnetron sputtering. In particular, we studied the high temperature tribological properties and the cutting performance in real service drilling tests and compared the results with a monolayer Ti0.47 Al0.46 N reference film. Dry sliding experiments were performed using a pin-on-disc tribometer at room temperature and at 650 °C with Al2 O3 balls as counterparts. The drilling performance of the coatings was evaluated at cutting speeds in the range of 50–200 m/min. Wear of the drills in different zones (chisel edge and flank edge) was mapped after every 15 holes. Highlights: Effect of Cr on tribological and cutting performance of multilayered TiAlCrN films. Wear rate of films was independent of the chemical composition at room temperature. At high temperature wear resistance of Cr rich films is much better than TiAlN. Cutting performance of Cr rich films is better due to the growth of a Cr-O tribolayer.